The Use of Zirconia for Implant-Supported Fixed Complete Dental Prostheses: A Narrative Review - Chiara Cinquini; Fortunato Alfonsi; Vincenzo Marchio; Francesco Gallo; Francesco Zingari; Alessandro Remigio Bolzoni; Stefano Romeggio; Antonio Barone (MDPI AG, 2023)
The success of implant-supported fixed complete dental prostheses (ISFCDPs) depends on multiple factors: some are related to the fixtures, such as fixture material, surface characteristics, positioning, and type of connection to prosthetic components; others are related to the prostheses, such as design and materials used. Zirconia is a material widely used in fixed prosthodontics, whether on natural teeth or on implants, with excellent results over time. Regarding the use of zirconia for ISFCDPs, the 2018 ITI Consensus Report stated that "implant-supported monolithic zirconia prostheses may be a future option with more supporting evidence". Since CAD/CAM technology and zirconia are being continuously innovated to achieve better results and performances over time, a narrative review of the literature seems necessary to focus research efforts towards effective and durable solutions for implant-supported, full-arch rehabilitations. The objective of the present narrative review was to search the literature for studies regarding the clinical performance of zirconia-based ISFCDPs. According to the results of this review, the use of zirconia for ISFCDPs showed good clinical outcomes, with high survival rates ranging from 88% to 100% and prosthetic complications that were restorable by the clinicians in most cases.